Elevated risk of possible sarcopenia and weak muscle strength with higher dietary inflammatory index in Iranian breast cancer survivors: a cross-sectional study - Kianaz Shirinyfard Pilehrood; Gholamreza Askari; Mehran Sharifi; Mehdi Kargarfard; Sahar Saraf-Bank (BMC Nutrition)
Abstract Background Increased levels of inflammation in cancer patients and survivors can make them more prone to muscle wasting and sarcopenia. Diet can be an appropriate treatment for alleviating patient complications. Therefore, this study was performed to determine the association between sarcopenia and its components with the dietary inflammatory index (DII) among breast cancer survivors. Methods A total of 223 female breast cancer survivors were included in this research at the Cancer Prevention Research Center of Seyyed Al-Shohada Hospital and the Iranian Cancer Control Charity Institute (MACSA). Forty-three items of dietary inflammatory index (DII) were extracted from the Food Frequency Questionnaire. Sarcopenia detection was performed according to the Asian criteria. The linear and binary logistic regression was used to assess the association between sarcopenia and its components with DII. Results Participants in the highest DII quartile had significantly elevated risk of impaired hand grip strength and calf circumference in both crude and adjusted models. Moreover, individuals consuming a more pro-inflammatory diet displayed a greater risk of abnormal appendicular skeletal muscle index in the crude model. After controlling for potential confounders, participants in the top quartile of DII had a 2.992-fold greater risk of possible sarcopenia than those in the bottom quartile (P value = 0.035). In addition, a decreasing linear trend was observed between higher DII score and 0.059 and 0.349- units lower in appendicular skeletal muscle mass index and hand grip strength variables in the crude Model (P-value < 0.05). Conclusion Diets with more pro-inflammatory features might be associated with increased risk of possible sarcopenia, as well as its components especially muscle mass and strength in women recovering from breast cancer.